2013
DOI: 10.1016/j.bjid.2012.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of different mechanisms to the resistance to fluoroquinolones in clinical isolates of Salmonella enterica

Abstract: Efflux pump inhibitors may inhibit the major AcrAB-TolC in Salmonella efflux systems which are the major efflux pumps responsible for multidrug resistance in Gram-negative clinical isolates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 40 publications
(53 reference statements)
3
50
1
Order By: Relevance
“…Resistant typhoid strains, however, have been recently reported [9,24]. There are limited data, if any, reporting quinolone resistance among Egyptian typhoidal Salmonella isolates [15]. We showed that NA resistance increased from 0% in 1993 [16] to 15% in this study, which was similar to what was found (15%) in a report from Vietnam [25] and another (16%) from Japan [26].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Resistant typhoid strains, however, have been recently reported [9,24]. There are limited data, if any, reporting quinolone resistance among Egyptian typhoidal Salmonella isolates [15]. We showed that NA resistance increased from 0% in 1993 [16] to 15% in this study, which was similar to what was found (15%) in a report from Vietnam [25] and another (16%) from Japan [26].…”
Section: Discussionsupporting
confidence: 87%
“…There are limited data, if any, reporting quinolone resistance among Egyptian isolates of typhoidal Salmonella [15]. In this regard, we previously reported that all typhoidal Salmonella isolated from patients at Minia Governorate were sensitive to quinolones [16].…”
Section: Introductionmentioning
confidence: 99%
“…Rushdy et al 31 showed that five Salmonella isolates totally resistant to all quinolones had alterations in outer membrane proteins, including disappearance of some or all of these proteins: Omp-A, Omp-C, Omp-D, and Omp-F. The role of Omp loss in quinolone resistance was clarified in E. coli, 32 but is still unclear in Salmonella.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC M s for the major portion of the Salmonella strains here with citric and lactic acids were also observed about 1 pH unit lower at pH 4.1 and pH 4.2. Salmonella enterica also has efflux systems, and efflux pumps or overexpressed efflux pumps can contribute too many classes of chemical resistance [43]. Also, S. enterica has been shown to display arginine-dependent acid-resistance [44].…”
Section: Beier Et Almentioning
confidence: 99%